2002
DOI: 10.1002/jms.298
|View full text |Cite
|
Sign up to set email alerts
|

Identification of glucuronide conjugates of ketobemidone and its phase I metabolites in human urine utilizing accurate mass and tandem time‐of‐flight mass spectrometry

Abstract: The glucuronide conjugates of ketobemidone, norketobemidone and hydroxymethoxyketobemidone were identified in human urine post-intravenous administration of Ketogan Novum. The human urine was extracted on a mixed-mode solid-phase micro-column before analysis with liquid chromatography/electrospray ionization time-of-flight mass spectrometry (LC/ESI-TOF-MS) and tandem MS (MS/MS). Accurate mass and collision-induced dissociation product ion spectra were used for identification of the glucuronide conjugates. Two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
25
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 9 publications
1
25
0
Order By: Relevance
“…Liquid chromatography/mass spectrometry (LC/MS) and LC/MS/MS are powerful tools for directly detecting highly polar and nonvolatile conjugates; many research groups including our own have reported the detection of conjugates of various compounds using LC/MS and LC/ MS/MS [8][9][10][11][12][13][14][15][16][17][18][19][20]. We reported the identification of urinary psilocin glucuronide (PCG) by LC/MS and LC/MS/MS, and the optimization of its enzymatic hydrolysis conditions for urine, and showed that all PC excreted into urine was in the form of its glucuronide conjugate [15]; in the present study, this line of experiments has been extended to PCG and PC in human serum.…”
Section: Introductionmentioning
confidence: 99%
“…Liquid chromatography/mass spectrometry (LC/MS) and LC/MS/MS are powerful tools for directly detecting highly polar and nonvolatile conjugates; many research groups including our own have reported the detection of conjugates of various compounds using LC/MS and LC/ MS/MS [8][9][10][11][12][13][14][15][16][17][18][19][20]. We reported the identification of urinary psilocin glucuronide (PCG) by LC/MS and LC/MS/MS, and the optimization of its enzymatic hydrolysis conditions for urine, and showed that all PC excreted into urine was in the form of its glucuronide conjugate [15]; in the present study, this line of experiments has been extended to PCG and PC in human serum.…”
Section: Introductionmentioning
confidence: 99%
“…The task of metabolite identification has been greatly facilitated by recent developments in high resolution LC/MS technology [e.g., timeof-flight (ToF) and Fourier transform (FT) mass spectrometers], which allow for the determination of molecular formulae (Corcoran et al, 2000;Zhang et al, 2000;Sundstrom et al, 2002) and product ion formulae (Sleno et al, 2005) with minimal uncertainty. In addition, the specificity of list-dependent acquisition of MS/MS data for expected metabolites is improved (Castro-Perez et al, 2002).…”
mentioning
confidence: 99%
“…TOF technology uses high sensitivity in full-scan MS analysis along with enhanced selectivity due to the higher resolution and mass accuracy measurement. Hybrid Q-TOF analysers allow the determination of the chemical formula of precursor and product ions (Corcoran et al 2000;Zhang et al 2000;Sundstrom et al 2002;Sleno et al 2005), and they are being employed as one of the major LC-MS platforms for characterizing unknowns, such as TPs (Gómez-Ramos et al 2011).…”
Section: Introductionmentioning
confidence: 99%